2013
DOI: 10.1371/journal.pone.0062655
|View full text |Cite
|
Sign up to set email alerts
|

End of the Century pCO2 Levels Do Not Impact Calcification in Mediterranean Cold-Water Corals

Abstract: Ocean acidification caused by anthropogenic uptake of CO2 is perceived to be a major threat to calcifying organisms. Cold-water corals were thought to be strongly affected by a decrease in ocean pH due to their abundance in deep and cold waters which, in contrast to tropical coral reef waters, will soon become corrosive to calcium carbonate. Calcification rates of two Mediterranean cold-water coral species, Lophelia pertusa and Madrepora oculata, were measured under variable partial pressure of CO2 (pCO2) that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
73
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 45 publications
7
73
4
Order By: Relevance
“…No significant differences between treatments were observed among the different sampling times for both species (ANOVA, F 4,18 = 0.110, p = 0.739 for L. pertusa and F 4,30 = 0.138, p = 0.406 for M. oculata; Figure 1a,b). Our results are in accordance with two previous mid-term studies assessing the effects of OA on these same species, where no differences were observed after 6 months in L. pertusa [13] or 9 months of exposure in L. pertusa and M. oculata [21]. This suggests that, at least at mid-term, CWC are able to counteract the a priori more negative environment that lowered-pH oceans should create for calcifying organisms.…”
Section: Measured Parameterssupporting
confidence: 92%
See 3 more Smart Citations
“…No significant differences between treatments were observed among the different sampling times for both species (ANOVA, F 4,18 = 0.110, p = 0.739 for L. pertusa and F 4,30 = 0.138, p = 0.406 for M. oculata; Figure 1a,b). Our results are in accordance with two previous mid-term studies assessing the effects of OA on these same species, where no differences were observed after 6 months in L. pertusa [13] or 9 months of exposure in L. pertusa and M. oculata [21]. This suggests that, at least at mid-term, CWC are able to counteract the a priori more negative environment that lowered-pH oceans should create for calcifying organisms.…”
Section: Measured Parameterssupporting
confidence: 92%
“…These growth rates are comparable to those previously measured on the same CWC species using different techniques [19][20][21][22]. However, the average growth rate of L. pertusa observed in the experiment of Form and Riebesell [13] was about one order of magnitude lower than in previous works, probably due to the lower incubation temperature used by these authors (7.5 °C) compared to other studies (between 10 and 13 °C).…”
Section: Measured Parameterssupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, these species naturally exhibit slow growth and calcification rates, which range between ∼2 to 9 mm year −1 (Brooke and Young, 2009;Larcom et al, 2014;Lartaud et al, 2014) making them particularly vulnerable to the effects of future ocean acidification. Nevertheless, recent evidence from experimental studies suggests that cold-water corals can be resistant to low aragonite saturation states, and may even be able to calcify in undersaturated conditions (Form and Riebesell, 2012;Maier et al, 2013;Hennige et al, 2015), though at a reduced rate (Maier et al, 2009;Lunden et al, 2014a). The ability to maintain calcification under lowpH conditions has been explained by the capacity of cold-water corals to upregulate the pH of their internal calcifying fluid by up to 0.8 units (McCulloch et al, 2012;Wall et al, 2015).…”
Section: Introductionmentioning
confidence: 99%